2009
DOI: 10.1371/journal.pone.0007440
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: MicroRNA Expression Profiles Accurately Differentiate Patients with Relapsing-Remitting Disease from Healthy Controls

Abstract: Multiple sclerosis (MS) is a chronic inflammatory demyelinating disease of the central nervous system, which is heterogenous with respect to clinical manifestations and response to therapy. Identification of biomarkers appears desirable for an improved diagnosis of MS as well as for monitoring of disease activity and treatment response. MicroRNAs (miRNAs) are short non-coding RNAs, which have been shown to have the potential to serve as biomarkers for different human diseases, most notably cancer. Here, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
257
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(269 citation statements)
references
References 19 publications
8
257
2
2
Order By: Relevance
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As such, these miRNAs may be differentially expressed in other immunemediated diseases and have broader implications on CD4 T cell development and differentiation. It is well established that miRNAs play key roles in the development and function of Tregs (Gao et al, 2012;Josefowicz et al, 2012;Dooley et al, 2013), and differential expression of miRNAs have been found in patients with multiple sclerosis (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). To our knowledge none of the miRNAs identified in this study had been previously defined to play a role in Tregs.…”
Section: Discussionmentioning
confidence: 63%
“…While genetic studies have identified genes critical to the immune system as being potential risk factors (Baranzini et al, 2009b;De Jager et al, 2009;Beecham et al, 2013), many of the genetic contributors to this disease are unknown. An emerging area of interest in multiple sclerosis has been genetic regulation at the microRNA (miRNA) level (Du et al, 2009;Keller et al, 2009;Otaegui et al, 2009;De Santis et al, 2010;Guerau-de-Arellano et al, 2011;Noorbakhsh et al, 2011;Jr OeF et al, 2012;Smith et al, 2012;Gandhi et al, 2013;Ridolfi et al, 2013;Søndergaard et al, 2013). MiRNAs are small, non-coding RNA that regulate gene expression and, thus, modify cellular pathways and disease processes (Ambros, 2004;Bartel, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Otaegui et al [30] reported differential miRNA expression in PBMC from MS patients during remission and relapses. Another recent study described diverse miRNA expression profiles in whole blood cells of MS patients compared with healthy controls [31]. However, nothing is known about miRNA expression in various cell subpopulations and their importance during the differentiation and activation of lymphocytes in MS.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, a study defined hsa-miR-145 as a biomarker of MS with a specificity of 95%, a sensitivity of 97.6%, and an accuracy of 96.3% [45]. This microRNA was found to induce rearrangement of the actin cytoskeleton and nuclear rotation when overexpressed, affecting vital cellular functions such as cell migration, division and polarity.…”
Section: Activation Of T-and B-cellsmentioning
confidence: 99%